Hemodialysis improves endothelial venous function in end-stage renal disease - Silva,A.M.V. (2008)
The objective of the present study was to determine the acute effect of hemodialysis on endothelial venous function and oxidative stress. We studied 9 patients with end-stage renal disease (ESRD), 36.8 ± 3.0 years old, arterial pressure 133.8 ± 6.8/80.0 ± 5.0 mmHg, time on dialysis 55.0 ± 16.6 months, immediately before and after a hemodialysis session, and 10 healthy controls matched for age and gender. Endothelial function was assessed by the dorsal hand vein technique using graded local infusion of acetylcholine (endothelium-dependent venodilation, EDV) and sodium nitroprusside (endothelium-independent venodilation). Oxidative stress was evaluated by measuring protein oxidative damage (carbonyls) and antioxidant defense (total radical trapping antioxidant potential - TRAP) in blood samples. All patients were receiving recombinant human erythropoietin for at least 3 months and were not taking nitrates or a-receptor antagonists. EDV was significantly lower in ESRD patients before hemodialysis (65.6 ± 10.5) vs controls (109.6 ± 10.8; P = 0.010) and after hemodialysis (106.6 ± 15.7; P = 0.045). Endothelium-independent venodilation was similar in all comparisons performed. The hemodialysis session significantly decreased TRAP (402.0 ± 53.5 vs 157.1 ± 28.3 U Trolox/µL plasma; P = 0.001). There was no difference in protein damage comparing ESRD patients before and after hemodialysis. The magnitude of change in the EDV was correlated negatively with the magnitude of change in TRAP (r = -0.70; P = 0.037). These results suggest that a hemodialysis session improves endothelial venous function, in association with an antioxidant effect.